Poly(propylene)/carbon composite thin films obtained by pulsed electron‐beam deposition. Issue 7 (30th April 2018) - Jędrzejewski, Roman; Piwowarczyk, Joanna; Jędrzejewska, Anna; Kwiatkowski, Konrad; Baranowska, Jolanta
Abstract : For the first time pulsed electron beam deposition (PED) was used to deposit thin films composed of polymer‐carbon composite material. The targets were polypropylene‐carbon (PP/C) composites, with different carbon fillers: carbon black, nanotubes, or graphene. It was confirmed that coatings with composite structure were obtained – the PED method enables complex structures, including nanotubes, to be ablated whole from the target, transported toward substrate, and incorporated into the polymer matrix. These breakthrough results can contribute significantly to improved understanding of the mechanism of electron beam ablation of polymer and composite materials, and open up new possibilities for the deposition of complex composite thin films for use in, for example, advanced sensor applications. Abstract : For the first time, composite thin films have been successfully obtained from a Polypropylene/Carbon composite target using pulsed electron‐beam deposition . This technique preserves well both the polymer matrix and complex particles, such as nanotubes or graphene. These findings open up new perspectives for the deposition of complex composite materials as thin films for various applications, such as nanosensors.